Differences in Hyperandrogenism Related to Early Detection of Non-Classical Congenital Adrenal Hyperplasia on Second Newborn Screen - Bonnie McCann-Crosby; Mark C. Liang; Mitchell E. Geffner; Christina M. Koppin; Nicole R. Fraga; V. Reid Sutton; Lefkothea P. Karaviti; Gagandeep Bhullar; Mimi S. Kim (MDPI AG, 2023)
Screening for congenital adrenal hyperplasia (CAH) remains heterogenous across geographies-we sought to determine the proportion of non-classical CAH (NCAH) detection by one vs. two newborn screens (NBS) in two U.S. regions. Data were collected at tertiary centers in Houston (HOU) and Los Angeles (LA) on 35 patients with NCAH, comparing patients identified via the NBS vs. during childhood, 17-hydroxyprogesterone (17-OHP) levels, genotype, and phenotype. The NBS filter-paper 17-OHP levels and daily cutoffs were recorded on initial and second screens. In all, 53% of patients with NCAH in the HOU cohort were identified as infants via the second NBS. Patients identified clinically later in childhood presented at a similar age (HOU: n = 9, 5.5 ± 3.1 years; LA: n = 18, 7.9 ± 4 years) with premature pubarche in almost all. Patients in LA had more virilized phenotypes involving clitoromegaly and precocious puberty and were older at treatment onset compared with those identified in HOU by the second NBS (HOU: 3.2 ± 3.9 years; LA: 7.9 ± 4.0 years, p = 0.02). We conclude that the early detection of NCAH could prevent hyperandrogenism and its adverse consequences, with half of the cases in HOU detected via a second NBS. Further studies of genotyping and costs are merited.